2018
DOI: 10.3329/mediscope.v6i1.38940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary fiber on postprandial glucose in healthy adults

Abstract: Frequently and persistently raised glucose level causes numerous complications. So it is important to find out a component of diet that can improve glucose homeostasis after ingestion of food without causing any side effect or complication. The aim of this randomized controlled clinical trial study was to verify the effect of dietary fiber on postprandial blood sugar (PPBS).The study was carried out in a sample of fifty healthy adult subjects at the Department Physiology of Rajshahi Medical College during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Results suggest some reduction in postprandial glucose peaks at certain time points in the intervention group compared with placebo group. These results are in accord with recent studies that indicating significant lower blood glucose levels observed in test meals containing dietary fiber [31][32][33]. However, a higher blood glucose levels at 120 min in the intervention group could be attributed to the presence of slowly digestible starch in the formulated MMT peel powder belonging to the intervention group which digested between 20 min and 180 min [34].…”
Section: Glycemic Responsesupporting
confidence: 92%
See 1 more Smart Citation
“…Results suggest some reduction in postprandial glucose peaks at certain time points in the intervention group compared with placebo group. These results are in accord with recent studies that indicating significant lower blood glucose levels observed in test meals containing dietary fiber [31][32][33]. However, a higher blood glucose levels at 120 min in the intervention group could be attributed to the presence of slowly digestible starch in the formulated MMT peel powder belonging to the intervention group which digested between 20 min and 180 min [34].…”
Section: Glycemic Responsesupporting
confidence: 92%
“…Soluble fiber is closely linked to the glycemic index concept which associated with satiety, short-term gut hormone, glucose and insulin responses [41,50,51] due to its viscosity and gel-forming properties [52,53]. The water soluble dietary fiber forms a viscous solution or gel in the stomach that delay gastric emptying from the stomach to the small intestine and physically reduce the rate of starch digestion and absorption in the small intestine [53][54][55] by forming an effective unstirred layer in the intestinal wall [32]. Next, the changes in the solution viscosity influence glucose diffusion by exerting greater resistance and hence delay its transportation across the intestinal mucosa [56].…”
Section: Glycemic Responsementioning
confidence: 99%
“…Concerning glycemic control, Nansel, et al found dietary fiber to be associated with better glycemic control in youth with T1D as indicated by higher 1,5-anhydroglucitol and lower mean glucose from continuous glucose monitoring, as well as lower glucose variability as indicated by lower standard deviation and mean amplitude of glycemic excursions [ 29 ]. These glycemic benefits of fiber might be caused by a reduction in the rate of glucose absorption via its beneficial viscosity properties [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Soluble ber is closely linked to the glycemic index concept which associated with satiety, short-term gut hormone, glucose and insulin responses (39,48,49) due to its viscosity and gel-forming properties (50,51). The water soluble dietary ber forms a viscous solution or gel in the stomach that delay gastric emptying from the stomach to the small intestine and physically reduce the rate of starch digestion and absorption in the small intestine (51)(52)(53) by forming an effective unstirred layer in the intestinal wall (54). Next, the changes in the solution viscosity in uence glucose diffusion by exerting greater resistance and hence delay its transportation across the intestinal mucosa (55).…”
Section: Discussionmentioning
confidence: 99%